Quail-Black Soldier Fly Larvae (BSFL) Integrated Farming: Bioconversion Efficiency, Economic Viability, and Farmers’ Perception Toward Circular Agriculture - Sembada, Pria; Ayuningtyas, Gilang; Priyambodo, Danang; Pangestu, Puguh; Agustin, Adinda Dwina (Politeknik Pembangunan Pertanian Bogor, 2025)
Integration farming of quail with Black Soldier Fly Larvae (BSFL) has the potential to support a circular economy and offer various benefits for future sustainability. To promote sustainable farming systems, it is essential to examine farmers' perceptions and the factors that influence their adoption of such systems. The objective of this study was to understand the bioconversion of BSFL with quail excreta as substrate, the potential of integrated farming models, and farmers' perceptions of BSFL. This research was conducted from July 2023 to March 2024. The BSFL bioconversion data were collected through observational studies and measurement techniques. Production and economic performance data, along with farmers' perceptions, were obtained through a combination of observation, surveys, and in-depth interviews with 11 quail farmers. The collected data were analyzed using both descriptive and comparative methods, employing the statistical software MS Excel and SPSS 22. The findings indicated that the combination of organic phenolics added to quail feed and fermented excreta as a substrate for BSFL yielded the optimal bioconversion value. Another notable finding is that integrated quail farming yields enhanced economic performance due to its ability to generate added value. However, it is essential to note that farmers exhibited varying degrees of knowledge and perceptions regarding BSFL. In conclusion, this study highlights the importance of enhancing production performance, as well as economic, social, and environmental sustainability, by fostering a circular economy through an integrated approach of quail farming with BSFL. However, it is crucial to note that educational and training programs, as well as mentorship related to the technical aspects of quail-BSFL production, in conjunction with financial assistance, are essential to augment the adoption rate of this integrated approach.